Programa encontro com Fátima Bernardes: um espaço para a cidadania? - Silva, Laianny Martins (2017)
This research seeks to identify in the discussions presented by the program Encuentro con Fátima Bernardes points that promote questions related to citizenship, starting from the perspective worked by the English sociologist Marshall (1967), which unfolds in Civil, Political and Social Rights. For the development of the work was presented a synthesis history of communication and citizenship; The history of television in Brazil, tracing the history and the profile of the programs of the auditorium and the history of the development of TV Globo, besides the contextualization of the concepts and classification of the Journalistic Genres and their Formats, broadening the discussion with the Television Genres and the insertion in the Programming grid our object of study, the program Meeting with Fátima Bernardes. The corpus of the research was composed of ten editions of the Encuentro program, published in the months of October, November and December of 2016 and analyzed according to the bardiana perspective - Content Analysis - how many to the Thematic and Lexical criteria. Subsequently, we analyze the hybridism between journalism, entertainment, and the relationship with the auditorium that characterizes the program. To understand this relationship we analyzed aspects about (Tele) Journalism, seeking to identify in the themes presented in the program the news-values. We identify the Genders within the Meeting program, besides observing who has voice within the Program is how aspects related to citizenship are treated.